Financial depth and international trade: evidence from China. Issue 4 (2nd October 2019) - Sun, Hua-ping; Muganyi, Tadiwanashe
Abstract: There has been renewed interest in the link between financial development and trade amongst researchers. Financial development is a multifaceted concept that encompasses several dimensions; however, there is very limited empirical work on how these dimensions interact with international trade. This study offers insights into the link between financial depth (a dimension of financial development) and international trade utilising data from China's trade flows with 145 trading partners between the years 2000 and 2016. Employing the FGLS estimation approach, this study concludes the following: (1) Financial depth significantly influences China's international trade flows, with the direction of impact depending on the indicator of financial depth employed. (2) Remittances augment financial development in China and significantly influence international trade flows. (3) Banking crises in China's trading partner economies have a significant negative impact on trade flows. (4) Strategic economic partnerships particularly trade agreements play a positive role in enhancing China's trade flows.